Peran Lembaga Pendidikan Pariwisata di Era Digital Tourism - Adrian Agoes (Tourism Scientific Journal, 2020)
The development of digital tourism in Indonesia seems to occur quite rapidly. The tourism industry in Indonesia also looks relatively ready to face this era where quite a number of companies engaged in tourism have adopted digital tourism in their business models. Moreover, there has been a shift in the generation of tourism in the world towards millennial generation or Generation Y. Even now the latest generation has grown, namely Generation Z. Things that can not be avoided will provide a new environment in the development of the tourism industry. This next generation transition will also present new challenges, including for the Tourism Education Institute, especially in this case the Higher Education Institution. This article is a non-research article in which the author pours his thoughts on the problem being studied. The writing of this article is based on a review of sources relevant to this problem. In this article it was revealed that tourism education in Indonesia still has a role in the development of the tourism industry. The main role is in maintaining the values ??of tourism that have developed since the Baby Boomers, Generation X and continue to Generation Y and Generation Z, but by remaining open to the development of tourism 4.0 and its changes.